Transcription Factor Protein (TFP)-Trait Relationships During Sugarcane Internode Development - Frederik C. Botha; Annelie Marquardt (Agronomy)
Understanding how transcription factors regulate biomass accumulation and sucrose storage is essential for improving sugarcane productivity. In this study, we quantified transcription factor protein (TFP) abundance in sugarcane internodes across developmental stages and growth rates. These profiles were correlated with key biochemical traits, including lignin, glucan, hemicellulose, and sucrose content. From 7333 identified proteins, 205 were annotated as transcription factors spanning 22 families. By applying Pearson correlation followed by Partial Correlation with Information Theory (PCIT), we identified 46 high-confidence TFP-trait associations. Key regulators, such as ScMYB113, ScMADS15, and ScbZIP85, exhibited trait-specific roles, influencing sucrose storage and cell wall biosynthesis. Network topology revealed distinct transcriptional modules linked to biomass production, polysaccharide deposition, and intermediary metabolism. Notably, sucrose and lignin accumulation intensified after internode elongation ceased, highlighting shifts in transcriptional control during maturation. This study delivers the first protein-level regulatory map linking transcription factors to metabolic traits in sugarcane and provides a framework for targeting candidate regulators to enhance biomass quality and yield in bioenergy crops such as sugarcane.